Hip Arthroplasty in a Patient with Transfemoral Amputation: A New Tip - Hassan Boussakri; Ihab Alassaf; Samir Hamoudi; Abdelhalim Elibrahimi; Philbert Ntarataz; Abdelmajid ELMrini; Jean Francois Dumez (Case Reports in Orthopedics)
Femoral fractures in amputation stump are challenging injuries to manage. The authors describe a case of a 51-year-old patient with a right above knee amputation, who had a right hip femoral neck fracture. In this technical note, we describe a technical and surgical procedure with intraoperative tips and tricks, in which we use commonly available materials, for the safe management in such clinical situations.